2006
DOI: 10.1080/07481180600776028
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Two Death Education Programs for EMTs Using theTheory of Planned Behavior

Abstract: The goal of this study was to evaluate the effectiveness of two death education programs by comparing pretest and posttest scores of behavioral intentions and (reported) behavior of EMTs when at the scene of a death. After the interventions, the majority of EMTs intended to change their behavior at the scene of a death when compared to the control group. In a three-month follow-up study, the majority of EMTs who received the intervention (and made a death notification) changed their behavior. In this sample, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…Three themes emerged: an increased openness to looking at death constructs, greater understanding of personal beliefs regarding death in general and one's own death, and a reduction in negative emotional state in the form of the participant's fear of death. These findings are in line with past research that found positive effects of death education on comfort and coping of participants (Bugen, 1980;Servaty & Hayslip, 1997;Smith-Cumberland, 2006;Wong, 2009).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Three themes emerged: an increased openness to looking at death constructs, greater understanding of personal beliefs regarding death in general and one's own death, and a reduction in negative emotional state in the form of the participant's fear of death. These findings are in line with past research that found positive effects of death education on comfort and coping of participants (Bugen, 1980;Servaty & Hayslip, 1997;Smith-Cumberland, 2006;Wong, 2009).…”
Section: Discussionsupporting
confidence: 95%
“…In a review of the literature, no studies were identified that addressed the usefulness of death education in assessing death attitudes of counselors-in-training. In studies involving other vocations (e.g., college students, nursing, physicians, and emergency medical technicians [EMTs]), death education on changing death attitudes and behavior and reducing death anxiety has produced positive and negative outcomes as well as mixed results (e.g., Bugen, 1980;Hurtig & Stewin, 1990;Johansson & Lally, 1990;Knight & Elfenbein, 1993;Maglio & Robinson, 1994;Servaty & Hayslip, 1997;Smith-Cumberland, 2006;Wong, 2009). Positive effects of death education include participants reporting more comfort and increased coping while addressing death and dying with others.…”
Section: Efficacy Of Death Educationmentioning
confidence: 99%
“…그 후 노령 인구의 증가와 평균수명의 연장으로 노화와 죽음에 대한 관심 이 더욱 증가하게 되어 (Jang, 2004) (Higgins, 1999;Smith-Cumberland, 2006).…”
Section: 이러한 죽음학은 20세기 이후 두 차례의 세계대전을 겪으면 서 인간의 본질적 가치와 생명 그리고 죽음에 관unclassified
“…A large number of studies have shown that educational programs have improved students' experience, confidence and competence of death notification. 9,11,25,26 After involving in the death notification role-play exercise, students valued the opportunity to learn how to complete the death notification process. The students also expressed the importance of having an opportunity to be trained in communication skills, particularly imparting death notifications before they are faced with communicating death notifications.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few exercises in death notifications have been evaluated. [9][10][11] To address the need for education in death notification for medical students, the Marathon Death, an experiential learning exercise that integrates valuable exercises and socioanalytic role-play, was created at the medical facility at Umeå University in Sweden as a method for illustrating and solving problems in human relations. In our context, it is used to teach and train medical students in delivering death notifications.…”
Section: Introductionmentioning
confidence: 99%